Eating Disorders: a behavioral analysis perspective. (Brazilian Journal of Behavioral and Cognitive Therapy, 2011)
This article presents a Behavioral Analysis comprehension of the “eating disorders”, specifically the “Anorexia Nervosa” and “Bulimia Nervosa”. Anorexic and bulimic practices were characterized in the three levels of selection by consequences. At the phylogenetic level, was discussed the evolution of man and its relationship with clinical features. In the ontogenesis, the operant relationship with the food was presented, pointing functional possibilities in various clinical situations. Finally, was discussed the aesthetic industry involvement in the capitalist culture, which sells the idea that a thin body removes aversive contingencies and can be bought or conquered, as an object for consumption dissociated from the individual who behaves and his history. The purging and restrictive feeding practices are a public health problem, in which the behavior analyst can intervene from the clinic, without neglecting the need for an understanding of the micro and macro cultural processes involved.
Keywords: behavior analysis; eating disorders; anorexia nervosa; bulimia nervosa